2017
DOI: 10.1186/s12913-017-2080-z
|View full text |Cite
|
Sign up to set email alerts
|

Meaning and barriers to quality care service provision in Child and Adolescent Mental Health Services: Qualitative study of stakeholder perspectives

Abstract: BackgroundDefining quality in health presents many challenges. The Institute of Medicine (IOM) defined quality clinical care as care that is equitable, timely, safe, efficient, effective and patient centred. However, it is not clear how different stakeholders within a child and adolescent mental health service (CAMHS) understand and/or apply this framework. This project aims to identify key stakeholders“ understanding of the meaning of quality in the context of CAMHS.MethodThe study sample comprised of three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…A call for intersectoral collaboration as a way to streamline services and efficacy has been proposed in previous studies and reviews [25,28]. The lack of a standardized protocol or tools for quality measurement can create confusion among providers, what stakeholders can expect from each provider and how caretakers or patients perceive as effective or efficient [22]. Educators involved in school health initiatives received no training in identifying atrisk students or those exhibiting symptoms of mental and neurological disorders, which were often defined as defiance or behavioural issues.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A call for intersectoral collaboration as a way to streamline services and efficacy has been proposed in previous studies and reviews [25,28]. The lack of a standardized protocol or tools for quality measurement can create confusion among providers, what stakeholders can expect from each provider and how caretakers or patients perceive as effective or efficient [22]. Educators involved in school health initiatives received no training in identifying atrisk students or those exhibiting symptoms of mental and neurological disorders, which were often defined as defiance or behavioural issues.…”
Section: Resultsmentioning
confidence: 99%
“…Continuity of care and follow-up by providers with their respective patients was considered appropriate and satisfactory by patients and primary caregivers. A patient-led treatment plan, that is meeting patients' or caregivers' expectations, however does not assist in determining overall quality [22]. Despite the overwhelming positive attitude of primary caregivers in the study, there is still a need to utilize meaningful, validated, and quantifiable tools for providers and policy makers to determine quality assurance [22].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Early interventions in psychoses has led to a growing worldwide interest in early and timely care for young people with all mental disorders (Birchwood & Singh, 2013;Cotton et al, 2016;Csillag et al, 2016;Jacobs, 2016;Malla et al, 2016;Nolin, Malla, Tibbo, Norman, & Abdel-Baki, 2016;Patton et al, 2016). Involving multiple stakeholders in youth mental health: teachers in schools/colleges, general practitioners, and various governmental and non-governmental organizations who work closely with the youth in the community is critical to this effort (Axelrod et al, 2002;Malla, Margoob, et al, 2019;Svirydzenka, Ronzoni, & Dogra, 2017). However, there is a dearth of published literature on assessing the views of diverse stakeholders on youth mental health in developing countries (broadly) and/or in India (more specifically).…”
Section: Introductionmentioning
confidence: 99%
“…A recent comprehensive review classified barriers to ROM implementation in three categories: related to the patient/clinician (eg, concerns about confidentiality, beliefs that measures are no better than clinical judgement), organization (eg, a lack of training resources), and system (eg, norms around ROM, competing demands) 40 . More specifically, studies have identified barriers, including a lack of information technology, 41‐43 time burden, 42,44‐46 perceived lack of measure validity/relevance, 34,42,44,45,47,48 lack of leadership commitment, 42‐44,49 lack of training, 41,43,45,47,50 and fear of how outcomes might be used 42,44 …”
Section: Introductionmentioning
confidence: 99%